A relação dos professores de matemática com o processo de transposição didática: apoios na interdisciplinaridade na contextualização e na complexidade do saber. - Wagner, Rosemeire Rodrigues (2006)
This research aims to investigate the conceptions of the Mathematics teachers related with the process of Transference of Didactical Knowledge – through the relationship inter-disciplines and contextualization – and the relation it establishes with the complexity of the knowledge. It’s also aimed to search theoretical basis towards the understanding of what the complexity, the inter-discipline and the contextualization of knowledge and the relationship of those queries with the process of didactical transference. It is hypothetically assumed that the Mathematics teacher by the high hyper-expertise of knowledge which he works and stuck in the Cartesian Paradigm doesn’t worry about his formation as an epistemic subject and ends for formulating concepts based in the common sense. As a result we have the strong difficulty to understand and establish the relationship among such conceptions, the acceptance of the knowledge as something moving constantly and the process of didactical transference. As a piece of the most relevant data it is assumed that the contextualization and the inter-discipline are not actions, but epistemic conceptions on which the process of didactical transference is based, through the complexity of the knowledge. And the contextualization is essential condition for the knowledge to be transferred from scientific to knowledge to be taught. To the teachers, however the contextualization of the knowledge is understood as relating the mathematical knowledge with their daily lives and complexity as something of difficult understanding. For example, the Mathematics.